Exploring farmers’ innovative behaviours after an agricultural entrepreneurial training – A qualitative analysis from Songhaï farmers in Benin - DALOHOUN, NOUGBÉGNON DANIEL (My University, 2017)
The study has made the argument that to enhance smooth agricultural innovations farmers need to embed in institutional settings enabling them to acquire capacities to innovate. It builds on the assumption that entrepreneurship implies innovative behaviours. A way to then equip farmers with innovative capacities is to train them on entrepreneurship.This paper, the seventh chapter and second sub-case (in my Ph.D. thesis), analyses how the type of training and learning process matters in ensuring continuous flows of innovations at farmers’ level.It uses Songhaï farmers as units of analysis and discusses evidence of these farmers’ innovative behaviours as the results of their participation at the Songhai entrepreneurial training program. The case answers the question of how have the Songhaï farmers being innovating. It assumes that the conditions under which the farmers set up agricultural businesses (the means and how these means are acquired), the types of the activities they have been undertaking provide the ground for identification of their innovation capacities.
Keywords: Agriculture; development; entrepreneurship; farmers; innovation; Songhaï.